On the potential intermediacy of PhIBr2 as a brominating agent. Issue 43 (18th October 2022) - Tania,; Molino, Andrew; Sharp-Bucknall, Lachlan; Wilson, David J. D.; Dutton, Jason L.
Abstract : PhIBr2 has been invoked as a brominating agent, however PhIBr2 does not appear to exist but rather forms PhI and Br2, with Br2 being responsible for bromination. Abstract : PhIBr2, first purported to exist over 100 years ago, has been subject of few reports due to its low stability. However, a recent publication proposes a reaction of PIFA (PhI(OC(O)-CF3 )2 ) with TMSBr to form PhIBr2 in situ and demonstrated its efficacy in aryl brominations. This report investigates this synthesis by replicating bromination reactions claiming to use in situ PhIBr2 as described. The spectroscopical and computational results indicate formation of PhI and Br2 where Br2 is responsible for bromination and no supporting evidence for invoking PhIBr2 as an intermediate is found.